ANALISIS KEBUTUHAN TENAGA PERAWAT DENGAN MENGGUNAKAN METODE WORKLOAD INDICATOR OF STAFFING NEEED (WISN) DI RUANG RAWAT INAP RSUD LAPANGAN SAWANG KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Lasaib, Armin A (Program Studi Pendidikan Olahraga STKIP Kie Raha Ternate, 2025)
ABSTRACT Human resources (HR) is one of the dominant indicators of the success of a hospital. Number of professionals, adequate and high-quality human resources are expected to be in accordance with their duties and functions. The reach scope and quality of health services depend on the capacity and quality of human resources. Inadequate human resources can result in a high workload on nurses. The purpose of this study was to analyze the needs of nurses by using the Workload Indicator Of Stafing Need (WISN) method in the inpatient room of the Lapangan Sawang General Hospital, Siau Tagulandang Biaro Regency. This study was an observational analytic study using the Workload Indicator Of Staffing Need (WISN) method conducted in the inpatient room of the Sawang Field General Hospital, Siau Islands Regency Tagulandang Biaro from October 2018 to April 2019. The samples were all nurses working in the inpatient room as many as 42 people. The results showed and that the need of nurses in the Dahlia inpatient room, inpatient ward, Anggrek inpatient, Seruni inpatient, and inpatient room were 18, 8, 15, 12 and 12 respectively. It can be concluded that the need of nurses in the inpatient room at the Lapangan Sawang General Hospital Siau Islands Regency Tagulandang Biaro are 24 nurses in total. Is recommended that the hospital do additional nurses, in order to reduce the excessive workload. So, it can improve the quality of services in the inpatient room and the WISN method can also be used in determining the needs of health workers in each unit in the hospital. Key Word: WISN, Nurses, Inpatien Room